ANALISIS DEIKSIS PADA FILM “LOSMEN BU BROTO” - Tanjung, Yessi; Anggraini Ginting, Dinda; Sabrina Barus, Elsa; Lubis, Fitriani (FKIP, Universitas Palangka Raya, 2023)
Deixis is a word or phrase whose reference is not fixed. This research examines the various kinds of diexistence contained in each story conveyed by each character in the film